2022
DOI: 10.3389/fimmu.2022.878630
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Profile Based on ART Delay in Vertically Infected HIV-1 Youths Is Associated With Inflammatory Biomarkers and Activation and Maturation Immune Levels

Abstract: Early antiretroviral treatment (ART) in vertically acquired HIV-1-infection is associated with a rapid viral suppression, small HIV-1 reservoir, reduced morbimortality and preserved immune functions. We investigated the miRNA profile from vertically acquired HIV-1-infected young adults based on ART initiation delay and its association with the immune system activation. Using a microRNA panel and multiparametric flow cytometry, miRNome profile obtained from peripheral blood mononuclear cells and its association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The age at ART initiation was not considered a matching variable but the reference group of children with PHIV with persistent viral control showed an early age at ART introduction. The results could be in agreement with previous studies in which our group identified soluble profiles of proteins and miRNAs based on ART delay in PHIV infected patients [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The age at ART initiation was not considered a matching variable but the reference group of children with PHIV with persistent viral control showed an early age at ART introduction. The results could be in agreement with previous studies in which our group identified soluble profiles of proteins and miRNAs based on ART delay in PHIV infected patients [ 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some of these host cell miRNAs play a role in interfering with the establishment of latent HIV-1 infection [ 11 , 12 ], while others promote cell activation and HIV-1 latency [ 13 , 14 ]. Interestingly, HIV-1-infected cells differentially express cellular miRNAs depending on whether the virus is productive or latent [ 15 ], thereby marking them as possible candidates for biomarkers of disease progression [ 16 , 17 ]. In contrast to the numerous studies identifying host cell miRNAs and elucidating their role in the regulation of HIV-1 infection, there remains a paucity of information regarding HIV-1-encoded miRNAs and their role in controlling viral replication [ 1 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%